PENGARUH PENGALAMAN AUDITOR DALAM MERESPON INFORMASI PERSUASIF AUDITEE - Sigit Wira Pratama; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
In  practice,  Auditor’s  perception  and  preference  about  the degree  of  importance  of government  procurement  control system  are  different  between  them.  And  dualism  of information that auditee gives to auditor, makes auditor have to respon in manner of completion of audit task and provided assurance opinion. Many factors, that influence auditor’s perception and respon, one of them is auditor’s audit experience. This study examines how auditor’s audit  experience influence auditor perception and preference about the degree of importance of government procurement control system and influence in auditor’s respon about persuasiveness of information provided by auditee. Research sample are auditors  who  work  in Indonesian Supreme Audit  Board  (head office and representative  office).  The  result  indicates  that  auditor’  experience  have  influence auditor’s respon in two condition management low and high ratings. However, this study do not explain the influence of auditor’s experience in perception and preference about the degree of importance of government procurement control system.